Nazwy zespołów i tytuły utworów disco polo. Rekonesans onomastyczno-kulturowy - Bogusław Skowronek (Annales Universitatis Paedagogicae Cracoviensis. Studia Linguistica, 2022)
In the article, I discuss the names of disco polo bands (disco polo is a kind of Polish pop music) and songs. I analyse the names from the linguistic and cultural perspective. I also highlight the external contexts. I also treat the onomastic layer of disco polo as a sign of cognitive conceptualisations, being the basis of the creation of images of the world in the lyrics.